2012
DOI: 10.1074/jbc.m112.369975
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Polynucleotide Kinase Phosphatase and the DNA Repair Protein XRCC1 Is Critical for Repair of DNA Alkylation Damage and Stable Association at DNA Damage Sites

Abstract: Background: XRCC1 interacts with multiple DNA repair proteins. Results: Identification of mutant versions of XRCC1 that are defective in binding with a different single partner. Conclusion:Interaction between XRCC1 and polynucleotide kinase 3Ј-phosphatase is critical for the retention of XRCC1 at DNA damage sites and DNA damage repair. Significance: Insights into function of one of three DNA end processing factors that bind to the same region of XRCC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 50 publications
3
33
2
1
Order By: Relevance
“…Della-Maria et al (14) utilized this system, without the addition of psoralen, to study the recruitment of XRCC1 and PNKP to the sites of laser-induced damage. Without psoralen to create cross-linked adducts, the authors proposed that this system generated free radical-induced SSBs in the irradiated region with no γH2AX foci detected (14).…”
Section: Uv Wavelengths To Induce Of Dna Damagementioning
confidence: 99%
See 2 more Smart Citations
“…Della-Maria et al (14) utilized this system, without the addition of psoralen, to study the recruitment of XRCC1 and PNKP to the sites of laser-induced damage. Without psoralen to create cross-linked adducts, the authors proposed that this system generated free radical-induced SSBs in the irradiated region with no γH2AX foci detected (14).…”
Section: Uv Wavelengths To Induce Of Dna Damagementioning
confidence: 99%
“…Della-Maria et al (14) utilized this system, without the addition of psoralen, to study the recruitment of XRCC1 and PNKP to the sites of laser-induced damage. Without psoralen to create cross-linked adducts, the authors proposed that this system generated free radical-induced SSBs in the irradiated region with no γH2AX foci detected (14). Recruitment kinetics of enhanced yellow fluorescent protein (YFP) fused XRCC1 showed a longer time to peak recruitment (~18 min) and retention of XRCC1 at the damage site for more than an hour (14).…”
Section: Uv Wavelengths To Induce Of Dna Damagementioning
confidence: 99%
See 1 more Smart Citation
“…The three most important polymorphic variants of this gene are as follows: in codons 194 (Arg → Trp), 280 (Arg → His), and 399 (Arg → Gln) (Duell et al, 2002;Berquist et al, 2010). Polymorphism in codon 399 in c c exon 10 affects its central domain, required for the activation of base repair, leads to amino acid substitu tion of arginine to glutamine, modifying the activity of the product and increasing the sensitivity of the genome to DNA damaging factors, including alkylat ing agents (Della Maria et al, 2012). It was also found that some alleles of gene XRCC1 affect carcinogenesis (Tudek, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Имеется три наиболее важных полиморфных варианта этого гена: в кодонах 194 (Arg → Trp), 280 (Arg → His) и 399 (Arg → Gln) (Duell et al, 2002;Berquist et al, 2010). Полиморфизм кодона 399 в 10-м экзоне затрагивает его центральный домен, необходимый для активации репа-рации оснований, приводит к замене аминокислот арги-нина на глутамин, изменяя активность продукта и увели-чивая чувствительность генома к ДНК-повреждающим, в том числе алкилирующим, агентам (Della-Maria et al, 2012). Установлено также, что некоторые аллели гена XRCC1 влияют на канцерогенез (Tudek, 2007).…”
Section: влияние комбинаций различных генотипов на индивидуальную преunclassified